1982
DOI: 10.1063/1.442971
|View full text |Cite
|
Sign up to set email alerts
|

Importance of initial and final states as intermediate states in two-photon spectroscopy of polar molecules

Abstract: Two-photon transitions may proceed via a mechanism not involving virtually excited intermediate states. For some examples, it is shown numerically that this mechanism may account for the largest contribution to the two-photon cross section in polar molecules, if the dipole moment strongly alters with excitation. Possible consequences for the two-photon detection of "forbidden" states in polar polyene systems are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 16 publications
6
83
0
Order By: Relevance
“…This is motivated by static dipole moments observed to differ from zero for the S 0 and the S 2 states of lattice distorted DPOT. 35,36 We take these transition probabilities as ''intrinsic,'' though dependent on the lattice environment. A complicated intensity pattern is expected from the linear combination of the moments through the S 1 -S 2 state mixing.…”
Section: Two-photon Excitation "Tpe…mentioning
confidence: 99%
See 1 more Smart Citation
“…This is motivated by static dipole moments observed to differ from zero for the S 0 and the S 2 states of lattice distorted DPOT. 35,36 We take these transition probabilities as ''intrinsic,'' though dependent on the lattice environment. A complicated intensity pattern is expected from the linear combination of the moments through the S 1 -S 2 state mixing.…”
Section: Two-photon Excitation "Tpe…mentioning
confidence: 99%
“…Following the discussion in Ref. 36, we separate the contributions of the ͉i͘ϭ͉g͘ and ͉i͘ϭ͉e͘ states in the sum of Eq. ͑15͒ leading to…”
Section: Two-photon Excitation "Tpe…mentioning
confidence: 99%
“…In the context of multiphoton absorption, Meath and Power demonstrated that the twolevel approximation is indeed never valid when deployed with a minimal-coupling Hamiltonian, since this kind of formulation requires sum rules to be applied over all levels in order to secure a usable result for the quantum amplitude [12]. It is interesting to reflect that the results of the theorem delivered in the present paper apply to both forms of coupling, addressing the matrix elements of both momentum and electric dipole operators.…”
Section: Discussionmentioning
confidence: 99%
“…With the typical intensity levels of pulsed laser light, there arises a significant probability for two or more photons to interact simultaneously (within the limits of quantum uncertainty) with each optically distinct center. Although the materials that are most effective for the utilization of optical nonlinearity in frequency conversion (especially second harmonic generation, SHG) are those whose energy level structures are significantly more complex than atoms, the two-level approximation has received wide application in such a context [5,[11][12][13][14][15][16][17][18]; it not only delivers results of a relatively simple form, it also relates well to long-established concepts of chemical structure. A wealth of synthetic studies have built on the anticipated and oft-proven connection between 'push-pull' chromophore structures [19][20][21][22] (facilitating intramolecular electron transfer) and an enhanced second harmonic response.…”
Section: Introductionmentioning
confidence: 99%
“…a two-state model may be applied. 15,16,18,20,[22][23][24][25][26][27][28][43][44][45][46][47][48][49][50][51][52] To be clear, the assumption is that the character of the fluorescence emission process, including the effect of the probe radiation, is dominated by two electronic levels; it is not to be presumed that the state from which the fluorescence decay occurs is necessarily the same as the state initially populated by photoexcitation. …”
Section: Two-level Systemsmentioning
confidence: 99%